2016
DOI: 10.4067/s0034-98872016000600014
|View full text |Cite
|
Sign up to set email alerts
|

Modelo de gestión de listas de espera centrado en oportunidad y justicia

Abstract: Waiting lists for elective surgery are considered a major health policy concern in most countries of the world. The most common reason to explain this phenomenon is that demand exceeds supply. Traditionally, the management of waiting lists has been focused on timeliness of medical attention. The objective of this paper is to present a waiting lists management model that includes the concepts of timeliness and justice simultaneously. We designed a prioritization method based solely on medical criteria. We devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In Chile, the government has injected resources to minimize, in part, the problem of waiting lists, but it has not been enough. Some authors have tried to solve the problem with management tools, such as the proposal by Silva-Aravena et al [14], Cisneros [45], Julio et al [46]. Like the international literature, the works try to improve management through the opinion of physicians and to represent this experience with ad-hoc mathematical tools to show the reality of each health service in a particular way.…”
Section: Prioritization Systems In Chile: Recent Evidencementioning
confidence: 99%
“…In Chile, the government has injected resources to minimize, in part, the problem of waiting lists, but it has not been enough. Some authors have tried to solve the problem with management tools, such as the proposal by Silva-Aravena et al [14], Cisneros [45], Julio et al [46]. Like the international literature, the works try to improve management through the opinion of physicians and to represent this experience with ad-hoc mathematical tools to show the reality of each health service in a particular way.…”
Section: Prioritization Systems In Chile: Recent Evidencementioning
confidence: 99%
“…In Chile, some strategies have been developed to support the management of waiting lists. For example, Julio et al [56] proposed a management model based on clinical components that measure the timeliness and fairness in the prioritization of patients. Martinez et al [57] proposed a statistical survival model to predict the risk of patient mortality.…”
Section: Strategies For Patients' Prioritizationmentioning
confidence: 99%
“…Their results showed that doctors in general prioritized patients according to the severity of their condition, even when no formal policy for prioritization is in place. In [ 40 ], a rule-based prioritization criterion was implemented to improve the management of waiting lists, considering waiting time and justice. The study demonstrated that timeliness considerations are insufficient to manage waiting lists properly and that justice should be included in the prioritization models.…”
Section: Introductionmentioning
confidence: 99%